FINITE ELEMENT ANALYSIS AND OPTIMIZATION OF TOP BEAM STRUCTURE FOR ADVANCE SUPPORTING EQUIPMENT OF ARCH - MAO Jun; GUO GuangLing; XIE Miao (Jixie qiangdu)
To solve the problem of stubborn balance,improve the efficiency of tunneling,the design of advanced support equipment of arch. In order to study the structural stability of the device,the multi-point distributed static model of the advanced support roof is established based on the actual working conditions. The stress and displacement equations of the roof beam are listed according to the principle of force method and singular function method. The simulation results show that there is stress concentration in the supporting roof beam with maximum stress of 192. 71 MPa and safety factor of 1. 22. Finally,the design of the top beam structure is optimized by using the Design Explorer module in ANSYS Workbench. The simulation results show that the quality of the single roof beam is reduced by 7. 6%,the overall stress is reduced by 28. 3%,the safety factor is increased to1. 70,Indicating that the optimized support structure has good structural stability. The conclusion can provide a reference for the structure,size design and optimization of the advanced support equipment and similar support equipment.